Qawaid Fiqhiyyah: Analisis Berdasarkan Hubungan dengan Tasyri’, Urgensi dan Perspektif Fukaha dalam Kerangka Fiqh - Laudza Hulwatun Azizah; Mita Mita; Muhammad Wildan; Radiatul Hafifah; Lisnawati Lisnawati (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2025)
Qawaid Fiqhiyyah is an Islamic legal principle that serves as a guideline for establishing rulings based on applicable principles in various fiqh issues. This study aims to analyze the relationship between Qawaid Fiqhiyyah and the Islamic legislation process (tasyri’), as well as its urgency in the Islamic legal system. This research employs a normative method with a qualitative approach, referring to primary legal sources such as the Qur’an and Hadith, as well as the opinions of scholars from various schools of thought. The results indicate that Qawaid Fiqhiyyah plays a strategic role in ensuring legal certainty and flexibility in the application of Islamic law, making it a foundation for contemporary Islamic legislation. These findings affirm that an understanding of fiqh principles can enrich legal decision-making in a more contextual manner.